Characterisation of plastic zones around crack-tips in pure single-crystal tungsten using electron backscatter diffraction - Murphy, J; Wilkinson, A; Roberts, S (IOP Publishing, 2009)
Plastic zones around crack-tips in tungsten were characterised by electron backscatter diffraction (EBSD). Pre-cracks were made in ∼1mm square cross section beams of pure single-crystal tungsten using a spark erosion method. The beams were loaded at different temperatures to a range of stress intensity factors below the fracture toughness. High resolution EBSD patterns were recorded in a two dimensional array in the vicinity of the crack-tip on sectioned samples. Cross-correlation based analysis of these patterns was used to determine lattice rotations associated with the plastic deformation near the cracks. Crystal rotations in the plane of observation were found to dominate over rotations in other planes. For all specimens deformed above the brittle-to-ductile transition temperature, plastic zones were found to extend from the crack tips on along narrow bands along {110} planes. The sizes of the plastic zones and their associated lattice rotations were determined as a function of loading history. © 2009 IOP Publishing Ltd.